DELAY TO ACL RECONSTRUCTION IN PEDIATRIC AND ADOLESCENT PATIENTS IS ASSOCIATED WITH A LINEAR INCREASE IN THE RISK OF MEDIAL MENISCAL TEARS. Issue 7 (30th July 2021) - Kolin, David A.; Dawkins, Brody; Park, Joshua; Fabricant, Peter D.; Gilmore, Allison; Seeley, Mark; Mistovich, R. Justin
Background: Anterior cruciate ligament (ACL) tears are frequently associated with meniscal tears. Previous studies have shown that secondary meniscal tears—occurring after the initial ACL injury—are associated with greater delays from injury to ACL reconstruction (ACLR), but frequently use dichotomous categories of acute versus delayed ACLR. Purpose: As meniscal damage is likely accrued constantly over time, we investigated the variability of concurrent meniscal injuries as a function of time from injury to ACLR in a pediatric and adolescent population. Methods: We performed a retrospective review of all patients ≤18 years who underwent an ACLR between 2014 and 2018 at one of two tertiary academic hospitals. Outliers were excluded if time from injury to ACLR was greater than 78 weeks. Records were reviewed to assess patients' dates of injury and surgery. The prevalence of concurrent medial and/or lateral meniscal injury was evaluated at the time of surgery for each patient. Adjusted relative risks (ARRs) of meniscal injury were calculated using Poisson regression models adjusted for age, sex, and body-mass index. Logistic regression was used to model the predicted probability of medial meniscal tears. Results: 546 patients met inclusion criteria. The mean age of participants was 15.3 years (S.D., 1.6), and 277 (50.7%) patients were male. Overall, 344 (63.0%) patients had a meniscal tear. 169 (49.1%) tears occurred at the medial meniscus, and 257 (74.7%) occurred at the lateral meniscus (Table 1). Compared to females, males had a greater risk of lateral meniscal injury (ARR, 1.46; 95% CI, 1.20-1.77) but not medial meniscal injury (ARR, 1.01; 95% CI, 0.77-1.31) (Figure 1). When considering all meniscal tears, time from injury to ACLR was not associated with increased risk of a tear (ARR, 1.01; 95% CI, 1.00-1.01). However, for medial meniscal tears, there was a significant association between time from injury to ACLR, in weeks, and meniscal tears (ARR, 1.02; 95% CI, 1.01-1.03, P = 0.003). A ten-week delay was associated with a 20% increased risk of medial meniscal injury (Figure 2). Conclusion: In pediatric and adolescent ACLR patients, the risk of any meniscal injury was not associated with delay from injury to surgery. However, the risk of medial meniscal injury increased by 2% each week from injury to surgery. Figure 1. Risk ratios for medial, lateral, or any meniscal tear (medial or lateral) adjusted for age, sex, and body-mass index Figure 2. Predicted probability of medial meniscal tear